2009
DOI: 10.1002/eqe.966
|View full text |Cite
|
Sign up to set email alerts
|

Analytical fragility analysis of southern Illinois wall pier supported highway bridges

Abstract: SUMMARYAn analytical fragility analysis was conducted in order to characterize the seismic vulnerability of existing southern Illinois wall pier supported highway bridges to potential earthquakes. To perform this fragility analysis, a detailed inventory survey was first taken of the wall pier bridges identified in an earlier random sampling of southern Illinois priority emergency route bridges. From the survey three types of wall pier bridges were identified. Of those identified, hammerhead and regular wall pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 23 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…The results from this research are generally consistent with other studies on bridges in the NMSZ. When studying fragilities of wall pier bridges in Illinois, Bignell and LaFave found that overall, bridge systems in the region are expected to experience only moderate damage for the MCE‐level hazard, which is similar to the conclusions herein. Similarly, they noted that pier properties were important in the general bridge response, but in contrast to the study presented in this paper, they found that bearings (steel roller, low‐profile fixed, and elastomeric in some cases) had little influence on the bridge fragility.…”
Section: Results Of Parametric Studysupporting
confidence: 76%
“…The results from this research are generally consistent with other studies on bridges in the NMSZ. When studying fragilities of wall pier bridges in Illinois, Bignell and LaFave found that overall, bridge systems in the region are expected to experience only moderate damage for the MCE‐level hazard, which is similar to the conclusions herein. Similarly, they noted that pier properties were important in the general bridge response, but in contrast to the study presented in this paper, they found that bearings (steel roller, low‐profile fixed, and elastomeric in some cases) had little influence on the bridge fragility.…”
Section: Results Of Parametric Studysupporting
confidence: 76%
“…Although the single‐pier bridges have been addressed frequently in the literature, 10–18 the wall piers have been rarely evaluated 19‐25 and the safety index of these bridges is still questionable, in a design point of view, to promote comfort and economy in modern communities. Guidelines for the modern seismic design of the wall piers of reinforced concrete bridges based on employing special reinforcement details and requirements related to the minimum ductility of structural members ensure the occurrence of plastic behaviors and energy dissipation in severe earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Three methods are commonly employed to determine this: nonlinear time history, incremental dynamic, and capacity spectrum analyses, with time history analysis being the most commonly used tool (Banerjee and Shinozuka, 2007;Bignell et al, 2004;Shinozuka et al, 2000a;Mackie and Stojadinović, 2001;Kumar and Gardoni, 2014). Incremental dynamic analysis can also be used to determine the earthquake response of a structure and derive the fragility curve (Lu et al, 2004;Kurian et al, 2006;Liolios et al, 2011).…”
Section: Introductionmentioning
confidence: 99%